The urban change in modern Shanghai descript by urban maps, 1840s-1930s - Xi, Gao; Nu, Peng (International Planning History Society Proceedings, 2018)
The urban change in modern Shanghai is a complex process which fused a lot of reasons in many ways. It is also the most important window to understand the urban modernization in china coastal city. This paper described the process of urban modernization in modern Shanghai according the analysis of the map of modern shanghai urban renewal. It separated to three parts. The first part, from river to sea, new and old existed together. Following the port opening, the old Chengxiang area and the new settlements area dramatic existed together. The second part, from street to the road. The new city views in settlements influenced the old town. The administrative department initiated the original change in Chengxiang area concentrate on building roads. And the influence from old land shape to the settlement’s road plan was different in British and French settlement. The third part, port areas and the city. With the city development, the bund function changed. And the relationship of Shiliupu dock and Chengxiang area was intimate. The general city structure